Nuevas citas y localidades para los Odonata de la Argentina - Rodrigues Capítulo, Alberto (1988)
Distributionalliimits of thirty five species of Odonata from Argentina are extended studied; specimens belong to the collections of the Museo La Plata, Instituto de Limnología (Universidad Nacional de La Plata) and Instituto Miguel Lillo (Universidad Nacional de Tucumán). Five of the studied species are here recorded for the first time for Argentina, as well as the two genera to which they belong.